Green production-clean technology and eco-efficiency keys for sustainability (Periodicals of Engineering and Natural Sciences, 2021)
Preserving their place on the agenda of international platforms in recent years, green (clean/eco efficiency) technologies are one of the basic components of the important concept of achieving sustainable development. Eco efficiency associates economic production with environmental factors in an internal union of economic development and protecting the ecosystem, in addition to revealing the importance of sustainable development and green economy in all stages of economic production. Green production controls the effects of process, product and services on human health and the ecosystem, while also being an approach to increase the sustainable efficiency of production. Changes to production and product development stages affect the whole value chain of products and steps taken within the scope of green technologies in this situation should be evaluated with the holistic approach of Life Cycle Analysis (LCA). LCA within this scope assesses the total environmental effect to prevent transfer of environmental load from one stage to another.In this study, to leave a livable world for future generations, all aspects of the absolute relationships between green technologies and eco efficiency are dealt with and analysis of the current status in Turkey is performed.